Cognition-oriented treatments for older adults: A systematic review of the influence of depression and self-efficacy individual differences factors. Issue 6 (3rd July 2022) - Webb, Shannon L.; Birney, Damian P.; Loh, Vanessa; Walker, Sarah; Lampit, Amit; Bahar-Fuchs, Alex
ABSTRACT: The increasing prevalence of cognitive decline, mild cognitive impairment (MCI), and dementia with the aging population has led to scrutiny of the efficacy of cognition-oriented treatments (COTs) aiming to maintain functioning, and delay or prevent further cognitive decline. However, little is known regarding the role of individual differences patient-variables (such as depression, self-efficacy, and motivation) in moderating the efficacy of COTs. This systematic review aimed to identify and analyze COT trials which investigated the relationship between differences in these patient-variables and intervention outcomes for older adults across healthy, MCI, and dementia populations. Of the 4854 studies extracted from the systematic search, 14 were included for analysis. While results were mixed across interventions and populations, on balance, greater depression severity predicted poorer cognitive functioning, and improvement in depressive symptom severity may account for at least part of the cognitive benefits seen at post-intervention. These findings were strongest for studies of MCI populations, with there being limited evidence of a relationship for healthy older adults or those with dementia. Overall, this review demonstrates the need for further investigation into the role of individual differences and clinical variables – particularly depression symptom severity – in attenuating COT outcomes through larger sample, high-quality randomized controlled trials.